Overview of The Implementation of Effective SBAR Communication Techniques (Situation, Background, Assessment, Recommendation) on Weight Received By The Nurse In The 1st Class Inpatient Room at Lumajang Hospital - Endrawati, Intan; Yuwanto, Mahmud Ady (Blambangan Journal of Nursing and Health Sciences (BJNHS), 2024)
Background: Communication errors are accused of being one of the main reasons that endanger patients. Communication errors were found to be a contributing factor in 65% of serious medical incidents. Effective communication that can be used by fellow medical health workers is SBAR communication. SBAR Communication Actions can be implemented during patient weigh-in activities. Purpose: To find out the description of the implementation of SBAR effective communication techniques in the acceptance and acceptance activities by nurses in the 1st class inpatient room. Method: The data collection technique used in this final scientific work uses observation and interviews. Data analysis uses descriptive. Results: In this scientific work, the implementation of SBAR communication during acceptance by class 1 inpatient nurses was good and optimal. Conclusions and Suggestions: It was concluded that if the weigh-in in the treatment room was carried out well and optimally using the SBAR communication technique, therefore this was triggered by the majority of nurses having a bachelor's degree in nursing, which increased the level of nurses' knowledge about the importance of implementing communication using SBAR during the weigh-in in the room and To maintain good communication, it is recommended that the hospital schedule doctor visits in the room not during shift change times and can be implemented by the doctor.